2015
DOI: 10.1016/j.ijpsycho.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Posterior EEG alpha at rest and during task performance: Comparison of current source density and field potential measures

Abstract: Resting and task-related EEG alpha are used in studies of cognition and psychopathogy. Although Laplacian methods have been applied, apprehensions about loss of global activity dissuade researchers from greater use except as a supplement to reference-dependent measures. The unfortunate result has been continued reliance on reference strategies that differ across labs, and a systemic preference for a montage-dependent average reference over true reference-free measures. We addressed these concerns by comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 49 publications
6
41
0
Order By: Relevance
“…The present report extends the time scale of this linkage by an additional ten years in a larger, mostly independent sample of participants. Moreover, by virtue of using a substantially denser EEG montage (72 vs. 13 sites), the effects could be unequivocally matched the unique neuronal generator pattern identified with posterior EEG alpha (Tenke et al, 2011, 2015). …”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The present report extends the time scale of this linkage by an additional ten years in a larger, mostly independent sample of participants. Moreover, by virtue of using a substantially denser EEG montage (72 vs. 13 sites), the effects could be unequivocally matched the unique neuronal generator pattern identified with posterior EEG alpha (Tenke et al, 2011, 2015). …”
Section: Discussionmentioning
confidence: 90%
“…These limiting conditions (i.e. floor and ceiling effects) offer at least a partial explanation for the observation that prestimulus task-related alpha (auditory novelty oddball) was strongly correlated with overall alpha, but negatively correlated with net alpha (Tenke et al, 2015). This distinction is particularly important because early R/S Importance was an indicator for overall alpha, rather than net alpha, in this and our previous study (Tenke et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, structural imaging measures suggested greater cortical thinning over right posterior cortex in children at high versus low risk (Peterson et al, 2009), and alpha was inversely related to cortical thickness, although not directly to alpha asymmetry (Bruder et al, 2012). While these findings are intriguing, the relationship of resting to task-related alpha (e.g., Tenke et al, 2015), or between structural and functional brain measures, is complex and as of yet not fully understood, necessitating the use of more targeted paradigms and measures. A recent MEG study employing the steady-state visual evoked fields technique reported a robust emotional modulation of rTPJ activity in 15 healthy women and 20 clinically-depressed women without a family history of depression; however, this modulation was markedly reduced in 8 depressed patients having at least one parent with a recurrent MDD diagnosis (Moratti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%